A multiple hypothesis approach to explain species richness patterns in neotropical stream-dweller fish communities - Vieira, Thiago Bernardi (2018)
Social wasps play important ecological roles, such as the natural biological control of other arthropods as well as major components of the flower-visiting insect guild. Despite many studies focusing on the survey of these organisms in Brazil, information on the community structure of polistines in anthropized environmets is still rare. The goals of the present study were: i) to survey the social wasp fauna in an anthropized area in the transition of Cerrado and Atlantic Forest; ii) to investigate the efficiency of two sampling methods, namely active search for wasps and the use of attractive traps; iii) to investigate the performance of different attractive baits in the capture success of social wasps in the study area. Sampling of social wasps was conducted by actively searching for individuals and by using attractive traps. A total of 40 species was recorded, with Agelaia multipicta and Agelaia vicina species being the most frequently collected with attractive traps and Mischocyttarus cassununga by actively searching for wasps. In all analyses performed (except when comparing abundance of social wasps considering the molasses bait and the active search), actively searching for wasps was the best method. This is also highlighted by the fact that the time spent actively capturing polistines was considerably lower than the time (and costs) that the traps were left in the field. Active search, as demonstrated by previous studies, remains as the best capturing methodology when surveying Neotropical social wasps, either in natural or anthropized environments.